Detecting a potential safety signal of antidepressants and type 2 diabetes: a pharmacovigilance‐pharmacodynamic study. (28th July 2018) - Siafis, Spyridon; Papazisis, Georgios
Abstract : Aims: Recent data suggest that antidepressants are associated with incident diabetes but the possible pharmacological mechanism is still questioned. The aim of the present study was to evaluate antidepressant's risk for reporting diabetes using disproportionality analysis of the FDA adverse events spontaneous reporting system (FAERS) database and to investigate possible receptor/transporter mechanisms involved. Methods: Data from 2004 to 2017 were analysed using OpenVigil2 and adjusted reporting odds ratio (aROR) for reporting diabetes was calculated for 22 antidepressants. Events included in the narrow scope of the SMQ 'hyperglycaemia/new‐onset diabetes mellitus' were defined as cases and all the other events as non‐cases. The pharmacodynamic profile was extracted using the PDSP and IUPHAR/BPS databases and the occupancy on receptors (serotonin, alpha adrenoreceptors, dopamine, muscarinic, histamine) and transporters (SERT, NET, DAT) was estimated. The relationship between aROR for diabetes and receptor occupancy was investigated with Pearson's correlation coefficient ( r ) and univariate linear regression. Results: Six antidepressants were associated with diabetes: nortriptyline with aROR [95% CI] of 2.01 [1.41–2.87], doxepin 1.97 [1.31–2.97], imipramine 1.82 [1.09–3.06], sertraline 1.47 [1.29–1.68], mirtazapine 1.33 [1.04–1.69] and amitriptyline 1.31 [1.09–1.59]. Strong positive correlation coefficients between occupancy and aROR for diabetes were identified for the receptors M1, M3, M4, M5 and H1 . Conclusion: Most of the tricyclic antidepressants, mirtazapine and sertraline seem to be associated with reporting diabetes in FAERS. Higher degrees of occupancy on muscarinic receptors and H1 may be a plausible pharmacological mechanism. Further clinical assessment and pharmacovigilance data is needed to validate this potential safety signal.